1999
DOI: 10.1126/science.286.5443.1321
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an E6AP-UbcH7 Complex: Insights into Ubiquitination by the E2-E3 Enzyme Cascade

Abstract: The E6AP ubiquitin-protein ligase (E3) mediates the human papillomavirus-induced degradation of the p53 tumor suppressor in cervical cancer and is mutated in Angelman syndrome, a neurological disorder. The crystal structure of the catalytic hect domain of E6AP reveals a bilobal structure with a broad catalytic cleft at the junction of the two lobes. The cleft consists of conserved residues whose mutation interferes with ubiquitin-thioester bond formation and is the site of Angelman syndrome mutations. The crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
612
2
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(633 citation statements)
references
References 38 publications
18
612
2
1
Order By: Relevance
“…While these experiments demonstrate a crucial role for Ube3a in synaptic transmission and suggest that the fundamental defect may be in synaptic function, the mechanisms by which Ube3a regulates synaptic function remain to be elucidated. UBE3A encodes a HECT (homologous to the E6-AP carboxyl terminus) domain E3 ubiquitin ligase that catalyzes the addition of ubiquitin to lysine residues on substrate proteins, leading to the degradation of the ubiquitinated substrate protein [52][53][54][55][56][57][58][59]. Human genetic studies have identified several mutations that specifically disrupt the ubiquitin ligase activity of UBE3A while having no effect on protein expression or substrate interactions (Fig.…”
Section: Cellular and Molecular Underpinnings Of Asmentioning
confidence: 99%
“…While these experiments demonstrate a crucial role for Ube3a in synaptic transmission and suggest that the fundamental defect may be in synaptic function, the mechanisms by which Ube3a regulates synaptic function remain to be elucidated. UBE3A encodes a HECT (homologous to the E6-AP carboxyl terminus) domain E3 ubiquitin ligase that catalyzes the addition of ubiquitin to lysine residues on substrate proteins, leading to the degradation of the ubiquitinated substrate protein [52][53][54][55][56][57][58][59]. Human genetic studies have identified several mutations that specifically disrupt the ubiquitin ligase activity of UBE3A while having no effect on protein expression or substrate interactions (Fig.…”
Section: Cellular and Molecular Underpinnings Of Asmentioning
confidence: 99%
“…The catalytic cleft between the two lobes of the HECT domain is the site of many of the reported mutations. 49 Screening of the coding region by SSCP followed by direct sequencing is a relatively reliable way of detecting mutations. Frameshift, nonsense, and splice site mutations have been identified.…”
Section: Genetics Of Angelman Syndromementioning
confidence: 99%
“…In recent years, several general principles have emerged for protein-protein interactions in UBL transfer cascades [15][16][17][18][19][20][21][22][23][24][25][26] . Nonetheless, the selective coordination of enzymes within a particular UBL's cascade remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%